Rozrachunki po przełomie. Polskie przekłady z literatury bułgarskiej po 1989 r. Diagnozy i prognozy. Współczesność i tradycja / Reckoning after the turn. Polish translations of Bulgarian literature after 1989. Diagnoses and prognoses. The present time and - Juda, Celina (Przekłady Literatur Słowiańskich, 2009)
After 1989 the number of translations of Bulgarian literature into Polish decreased dramatically in comparison with the output of the previous 50 years. On the one hand, this seems to be caused by a complete change of the Polish state’s cultural policy principles, too little activity on the part of relevant institutions, or even giving up the obligation to create and support the inter-cultural dialogue or to mediate in this process. On the other hand, it is primarily market economy and interest of the media and not the efforts or commitment of the translators that are decisive factors for the number and quality of publications.